POSTREALITY REPRESENTATION OF DESIGN OF THE BUILDING OF THE GOVERNMENT CENTER OF BADUNG REGENCY, BALI - Mugi Raharja, I Gede (E-Journal of Cultural Studies; Volume 6, Number 3, November 2013, 2013)
ABSTRACT Postreality representation of design of the Building of the Government Center of Badung Regency is interesting to explore as it is designed using the most recent simulation. This study is intended to understand the form of representation, the process of the deconstruction of representation, and the meaning of the postreality representation of design of the Building of the Government Center of Badung Regency. As part of cultural studies, this study is a qualitative one. The theory of virtual space design, the theory of simulation, and the theory of deconstruction were eclectically used in the present study. The data were collected through observation, interview, and library research. The results of the study showed that the postreality representation of the design of the Building of the Government Center of Badung Regency represented the image of chronoscope, the image of the Government of Badung Regency, the appreciation of traditional architecture, hybrid of design, semiotization of design. The deconstruction process of the postreality representation of the design of the Building of the Government Center of Badung Regency represented the deconstruction of space and power. The postreality representation of design of the Building of the Government Center of Badung Regency implied the scientific and technological meaning. The meaning of the postreality representation of the Building of the Government Center of Badung Regency is implied from the integration of the computer technology and the field of fine arts and design.
Keywords: simulation, virtual, chronoscope, deconstruction, hybrid.